2010
DOI: 10.1111/j.1462-5822.2010.01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorting nexin 3 (SNX3) is a component of a tubular endosomal network induced by Salmonella and involved in maturation of the Salmonella-containing vacuole

Abstract: SummarySalmonella enterica serovar Typhimurium is an intracellular pathogen that grows within a modified endomembrane compartment, the Salmonellacontaining vacuole (SCV). Maturation of nascent SCVs involves the recruitment of early endosome markers and the remodelling of phosphoinositides at the membrane of the vacuole, in particular the production of phosphatidylinositol 3-phosphate [PI(3)P]. Sorting nexins (SNXs) are a family of proteins characterized by the presence of a phox homology (PX) domain that binds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 63 publications
5
58
0
Order By: Relevance
“…Depletion of the same factors had no inhibitory effect on SFV (not shown). Another hit, SNX3, has been reported to promote recruitment of Rab7a to Salmonella ‐containing vacuoles (SCVs) 25. Microscopy‐based localization of EGFP‐SNX3 during VACV infection indicated that SNX3 was recruited to MV‐containing vacuoles with similar kinetics as Rab7a (Figure S4).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Depletion of the same factors had no inhibitory effect on SFV (not shown). Another hit, SNX3, has been reported to promote recruitment of Rab7a to Salmonella ‐containing vacuoles (SCVs) 25. Microscopy‐based localization of EGFP‐SNX3 during VACV infection indicated that SNX3 was recruited to MV‐containing vacuoles with similar kinetics as Rab7a (Figure S4).…”
Section: Resultsmentioning
confidence: 98%
“…Some SNXs have also been reported to facilitate macropinosome maturation and function 23, 25, 59. Having identified SNX3 as a hit in the RNAi screen, we investigated its localization in cells that had internalized VACV MVs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown (41) that in epithelial cells LAMP1 recruitment on SCV is dependent on SopB and SNX3 interaction. SNX3 regulates trafficking in both the endocytic and secretory pathways (42)(43)(44), and depletion of SNX3 by siRNA only partially inhibits the recruitment of LAMP1 on SCV (41) suggesting that other host proteins could be involved in this process. Our results have shown that SipC is specifically required for LAMP1 recruitment, and SopB has no role in this process in macrophages.…”
Section: Discussionmentioning
confidence: 99%